O acontecimento da renda renascença: forças, subjetividades e maquinários no semiárido nordestino - Marllon Emanoel Souza Medeiros de Vasconcelos (2021)
The argument of this thesis is that the invention and unfolding of practices to lace renaissance lace constituted an event that produced ways of organizing, subjectivities and social machinery in the northeaster semi-arid region of Brazil. The practices of renaissance lace in the Brazilian semi-arid North-eastern began in Poção/PE, a small town in the Agreste region of Pernambuco, on the border with the Paraíba, and spread to other neighbouring cities, both in the Agreste of the same state and in Cariri in the neighbouring state. Regarding the notion of event, I consider it as a state of inversions in the power games that make existence emerge, and as creative events, irruptions that modify the established conditions, inverting them, putting them in new relationships, in contact with new strengths and new expressions. To think of history and territory as an event is to think of them as successions of a game of forces that enter into constant relationship and conflict to emerge in the reality of something new. In this perspective, tracing the lines of the renaissance income lace event is not just studying the product, or even the history of the people who produce it, but the history and territorialization of a constitution of a field of existence of its own, of a way of living, organizing, producing and being, which was invented, created, made possible around renaissance lace. To this end, we use the thought of Foucault (2010; 2017a) to outline a genealogical study, that is, a historical analysis that distances itself from universals and takes care to listen to its own history and follow the traces of its origins, always multiple and dispersed, focusing on the movements and relationships of singular events that made the birth of something that did not exist before possible. Additionally, we consider the thought of Deleuze and Guattari (2011; 2012a, 2012b) to outline the territorial aspects of this study, also composing cartographic research that questions how the territory of renaissance lace is populated, that is, how the game of forces, the multiplicities not yet organized, unconnected, not stratified were made, took shape and composed solid earth. As a result, we traced the lines of territorialization and constitution of the territory of Poção-PE and the movements and provenances of the invention of the first practices to lace renaissance on and from this territory. We outline the constitution of the lacemaker-body and its practices, which are imbricated in the way of life in this place. We mark the folds of a trade of lace, which begins as a small local trade, folds into a trade for travellers, trade with models in a workshop and, finally, enters into a factory becoming. We also traced the lines of opening with a local commerce and livelihood for the lacemakers, which took the form of a cooperative, in the organization of a renaissance lace fair and in the use of the city itself as a device for local commerce. Finally, we highlight how the factory development on this field of existence changed the local conditions of living of the lace, which has implied the precariousness and impossibility of local lacemakers living from their earnings from their activity. By highlighting the historical and territorial constitution of non-living conditions based on income, we consider their contingent and arbitrary character, that is, we emphasize the possibility and need for changes and transformations in this field of existence and in their ways of life so that living from renaissance lace is placed in a new opening of possibilities for the women who form the collective body of this practice.